National Estimates of Registered Sex Offenders in the United States: Is Double Counting a Problem? - Ackerman, Alissa R. (American journal of criminal justice, 2015)
The study of the content and makeup of the national registered sex offender population is in its early stages. Only a handful of studies have been conducted that assess the demographic, offense, and risk profiles of individuals on sex offender registries. This study analyzed data from the national sex offender registry to determine to what extent registered sex offenders were double counted, where they were double counted, and if there were any differences between individuals who were double counted and those who were not. Findings suggest that less than 3 % of the national estimate is double counted and that the individuals flagged as double counted were predominantly from a handful of states.